2020
DOI: 10.1093/aje/kwaa192
|View full text |Cite
|
Sign up to set email alerts
|

Are Physical Activity, Screen Time, and Mental Health Related During Childhood, Preadolescence, and Adolescence? 11-Year Results From the German Motorik-Modul Longitudinal Study

Abstract: Mental health (MH) and behavioural health are fundamental to a good quality of life. Only few studies investigated the influence between behavioural health (e.g., physical activity (PA), screen-time (ST)) and MH from childhood to adolescence. Therefore, this study investigated the relationship between PA and ST with MH by sex in a 11-year longitudinal cohort of German school children during 2003-2017. A German Motorik-Modul Cohort-Study subsample (N=686; 55.2% female; MageT1=5.57 years, SDageT1=1.00; MageT2=11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 58 publications
3
21
0
3
Order By: Relevance
“…The exploratory analysis revealed a positive effect of HRQoL pre-COVID-19 on PA within-COVID-19, especially in younger children and in females. Those results are in line with former studies [ 18 , 68 , 69 ], revealing a positive relation between HRQoL and PA. For example, Nigg et al [ 18 ] showed that mental and psychosocial health indicators predicted PA from early to later childhood and mostly in females, while there were few inverse relationships. A reason for this could be that children with higher HRQoL scores have more resources in different dimensions, e.g., cognitive and motivational resources, social resources (e.g., parental support), material resources (e.g., sports equipment) that allow them to stay active during a lockdown.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The exploratory analysis revealed a positive effect of HRQoL pre-COVID-19 on PA within-COVID-19, especially in younger children and in females. Those results are in line with former studies [ 18 , 68 , 69 ], revealing a positive relation between HRQoL and PA. For example, Nigg et al [ 18 ] showed that mental and psychosocial health indicators predicted PA from early to later childhood and mostly in females, while there were few inverse relationships. A reason for this could be that children with higher HRQoL scores have more resources in different dimensions, e.g., cognitive and motivational resources, social resources (e.g., parental support), material resources (e.g., sports equipment) that allow them to stay active during a lockdown.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, results indicate lower ST to be a protective factor for PA engagement. However, high PA levels pre-COVID-19 did not prevent ST during the lockdown situation [ 18 ]. At this point, studies on compensation behaviors for PA are missing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, we used our secondary definition of screen time, and thirdly, we restricted the study population to only include 11-year-olds to accommodate potential age trends. Lastly, since concerns have been raised regarding the importance of mental health [ 4 , 34 ], we decided to do a sub-analysis in which we adjusted for general wellbeing and stress in children.…”
Section: Methodsmentioning
confidence: 99%